2013
DOI: 10.1002/lary.23956
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for desaturation after tonsillectomy

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 39 publications
6
24
0
Order By: Relevance
“… 19,22,23 These complications range from oxygen desaturation below 90% that could be managed with supplemental oxygen to respiratory distress requiring reintubation. These findings are consistent with previous large‐scale studies showing that children with neurological comorbidities have an increased risk of respiratory problems following AT 36 . This information is valuable when counseling patients and families on the risks associated with AT in children with CP, as well as for the healthcare team when deciding how to best care for these complex patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 19,22,23 These complications range from oxygen desaturation below 90% that could be managed with supplemental oxygen to respiratory distress requiring reintubation. These findings are consistent with previous large‐scale studies showing that children with neurological comorbidities have an increased risk of respiratory problems following AT 36 . This information is valuable when counseling patients and families on the risks associated with AT in children with CP, as well as for the healthcare team when deciding how to best care for these complex patients.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with previous large-scale studies showing that children with neurological comorbidities have an increased risk of respiratory problems following AT. 36 This information is valuable when counseling patients and families on the risks associated with AT in children with CP, as well as for the healthcare team when deciding how to best care for these complex patients. Careful monitoring for secretion management is imperative as a child's baseline difficulty with secretion clearance may be exacerbated by postoperative sedation, pain, and swelling.…”
Section: Intraoperative and Anesthetic Risksmentioning
confidence: 99%
“…37 Much consideration and debate has been given to the question of admission and observation following tonsillectomy. There is wide variation in patterns of admission after tonsillectomy 54 and little standardization of monitoring practices. Such variation is central to the national dialogue on patient safety and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Because desaturation may occur with normal respiratory rate, measurements of respiratory rate without oximetry may fail to identify some patients at risk. 55 Work by Kieran and colleagues 54 comparing characteristics of those children who desaturated with those who did not in a consecutive sample of >4,000 patients provides a starting point, but much remains to be done to understand the cost-benefit value of admitting patients for monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the termination of an episode of obstructive apnea in children with OSA is reliant on an arousal from sleep and recruitment of the upper airway muscles to maintain airway patency, both of which are diminished by postoperative opioids. [14][15][16][17] To our knowledge, this is the first study to utilize tcPCO2 monitoring to measure hypoventilation in children undergoing adenotonsillectomy. Although limited, there have been previous studies that have demonstrated the potential intraoperative applications of tcPCO2 monitoring in both the adult and pediatric populations.…”
Section: Discussionmentioning
confidence: 99%